Photonic Crystals: Ordered 2D Colloidal Photonic Crystals on Gold Substrates by Surfactant‐Assisted Fast‐Rate Dip Coating (Small 10/2014). Issue 10 (May 2014) - Armstrong, Eileen; Khunsin, Worawut; Osiak, Michal; Blömker, Martin; Torres, Clivia M. Sotomayor; O'Dwyer, Colm
<x xml:space="preserve">Abstract</x> On page 1895, C. O'Dwyer and co‐workers report the surfactantinduced ordering of 2D and 3D colloidal crystal photonic crystals on metallic substrates by dip‐coating at fast rates. Ordered monolayer opals on conductive Au‐coated Si substrates behave as a 2D diffraction grating. This method allows high throughput, ordered colloidal crystal formation useful as nanomaterials templates for energy storage or functional materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>